La teoría del delito y su relación con las ciencias forenses. análisis del caso N°: 11901-2013-0088 - Sánchez Alvarez, María del Cisne (2023)
The scientific study of judicial evidence requires the application of a criminal investigation methodological system of forensic sciences, the results obtained are expressed in relation to physical, chemical and biological magnitudes. The evidence examined is characterized according to unique attributes, patterns, and structural features; conferring irrefutable degrees of statistical confidence on the results. The planning and methodical execution of the set of expertise related to the criminal act, allow the court to know the factual relationship of the punishable acts; The analysis of the evidence specified in the expert report (evidence), leads the judge of the case, to decide in a motivated manner in relation to the materiality of the infraction, and the responsibility of the accused. In the development of the proposed research: "The theory of crime and its relationship with forensic sciences. Analysis of case No.: 11901-2013-0088.” addresses the direct relationship of the structural elements of the theory of crime and its relationship with forensic sciences; For this purpose, we proceeded to analyze the structural elements of the criminal type of homicide (casuistry: case No. 11901-2013-0088), and its relationship with forensic sciences in terms of recognition, identification and evaluation of criminal evidence, such as expert results that support the adjudication of criminal responsibility of the prosecuted subject. The modality of the proposed research in terms of its approach: it is of a qualitative-descriptive type, where the characteristics of the variables are described: crime theory and forensic sciences applied to the specific case No.: 11901-2013-0088. Through the analytical study at the legal-dogmatic level of primary and secondary research sources, it was possible to conceptually synthesize the theoretical statements, interpretative level, and logical reasoning contained in case No.: 11901-2013-0088. Key Words: Criminal law, forensic sciences, crime theory, ballistics, criminal investigation.